PENGEMBANGAN INSTRUMEN EVALUASI HIGH ORDER THINKING SKILLS PADA MATERI JARINGAN HEWAN DENGAN BENTUK TWO-TIER MULTIPLE CHOICE QUESTION - AGUS PRAYITNO; Mufida Nofiana (Bioed : Jurnal Pendidikan Biologi, 2020)
Develop HOTS instruments in animal tissue material in the form of TTMCQ. Stages of development using the ADDIE model (Analysis, Determine, Development, Implementation, Evaluation). The research was conducted at SMA Negeri 1 Baturraden in September-October 2019. The subjects of this study were students of class X1 MIPA who had studied animal tissue material. The data analysis technique uses descriptive percentages. Mapping competencies, making learning objectives oriented to HOTS, agreeing on the material to be tested, making analysis of basic competencies, making learning indicators oriented to HOTS, making grids of HOTS questions, making HOTS questions in animal tissue  materials in the form of TTMCQ, set the rubric of the questions, making feedback to students about question, see the responses of students working on the questions, ask for responses from the teacher related to the questions, see the ability of students to work on questions in the form of TTMCQ, asking for continued development of TTMCQ questions for other biological materials including the excellence and weakness of the questions. Based on the results TTMCQ can calculate the HOTS of students, easy to make assessments, easy to process the results of tests compared by description test. In the other hands, there are problems with TTMCQ that are: difficult to develop questions with double questions, many cost for administering tests for questions, and student’s confuse with how to work in TTMCQ although given instructions both oral and written.